Response of sorghum (Sorghum bicolor) cultivars to nitrogen in non-traditional areas of Bihar - KUMAR, RAKESH; MAKARANA, GOVIND; MISHRA, J S; BHATT, B P (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at the research farm of ICAR-Research Complex for Eastern Region, Patna, Bihar during summer season of 2017 and 2018 to assess the production potential of grain sorghum (Sorghum bicolor L. Moench) cultivars as influenced by nitrogen levels. Treatments consisting 4 nitrogen levels (0, 40, 80 and 120 kg/ha) as main-plot and 09 sorghum cultivars including 5 hybrids (CSH 13, CSH 14, CSH 16, CSH 25 and CSH 30) and 04 varieties (CSV 15, CSV 20, CSV 23 and CSV 27) as sub-plot, were replicated thrice in a split-plot design. Results revealed that increasing levels of nitrogen from 40–120 kg/ha brought significant improvement in yield attributes and yield over control. Application of 120 kg N/ha produced a maximum grain yield (4.82 t/ha) and net returns (`79.5×103 /ha). Amidst cultivars, CSH 30 recorded significantly higher grain yield (4.92 t/ha), net returns (`82.3×103/ha), benefit-cost ratio (3.34) and economic efficiency (`843 ha/day). Hence, sorghum cultivar CSH 30 grown along with 120 kg N/ha was proved significantly better in terms of crop productivity and profitability in summer season, and may be adapted as choice of viable alternative in non-traditional area of eastern India.